Eat for life : the Food and Nutrition Board's guide to reducing your risk of chronic disease - Woteki, Catherine E.; Thomas, Paul R., 1953- (National Academy Press, 1992)
Gives guidelines for a dietary plan to reduce the risk of diet-related chronic diseases.